2017
DOI: 10.1587/transinf.2016edp7490
|View full text |Cite
|
Sign up to set email alerts
|

Data-Sparsity Tolerant Web Service Recommendation Approach Based on Improved Collaborative Filtering

Abstract: SUMMARYWith the ever-increasing number of web services registered in service communities, many users are apt to find their interested web services through various recommendation techniques, e.g., Collaborative Filtering (i.e., CF)-based recommendation. Generally, CF-based recommendation approaches can work well, when a target user has similar friends or the target services (i.e., services preferred by the target user) have similar services. However, when the available user-service rating data is very sparse, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Dynamic scheduling and offloading techniques have also been employed to get good performance in recommenders. 29,30 Fault-tolerant scheduling: Fault-tolerant scheduling has been investigated in grids, multiple processor systems, and general clouds. Little attention has been paid to fault-tolerant scheduling in mobile cloud environment.…”
Section: Related Workmentioning
confidence: 99%
“…Dynamic scheduling and offloading techniques have also been employed to get good performance in recommenders. 29,30 Fault-tolerant scheduling: Fault-tolerant scheduling has been investigated in grids, multiple processor systems, and general clouds. Little attention has been paid to fault-tolerant scheduling in mobile cloud environment.…”
Section: Related Workmentioning
confidence: 99%
“…Matrix factorization (MF) is a way to fill missing values in the user‐item purchase frequency matrix A . Commodity feature vectors are obtained by the MF model.…”
Section: The Ecfar Algorithmmentioning
confidence: 99%
“…Due to the objective function of the optimization problem in each iteration of the ALS can be split into independent least squares sub-problems, the ALS is suitable for distributed solution from a computational point of view. Formulas (8) and (9) can be executed in parallel on different workers to implement distributed computing.…”
Section: Matrix Factorization Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In [13], the authors suggested that a user can publish partial QoS data to the service community, so as to protect the remaining majority of QoS data. Similarly, in [14], the authors take the amount of published data as a tunable parameter and then transform the privacy-preservation problem into a multi-object optimization problem, so as to achieve a good tradeoff between data availability and data privacy.…”
Section: Related Workmentioning
confidence: 99%